Digitalisasi UMKM sebagai Strategi Meningkatkan Daya Saing di Era Ekonomi Digital - Morisson, Buci; Buci Morisson; Aula Ahmad Hafidh Saiful Fikri (E-Bisnis : Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
The digitalization of Micro, Small, and Medium Enterprises (MSMEs) has become a crucial strategy for enhancing competitiveness in the digital economy era. This study examines the utilization of digital technology by MSMEs in Bandung City, as well as the challenges and opportunities faced during the digital transformation process. Employing a literature review approach and the Systematic Literature Review (SLR) method, this research identifies the impact of the digital economy on MSMEs, including the use of cloud computing for data storage and analytics to understand consumer behavior. Despite challenges such as digital literacy gaps and budget constraints, support from the government through initiatives like the UMKM Go Digital Movement and Bandung Smart City has accelerated digitalization efforts. These programs provide significant training and assistance, with over 5,000 MSMEs receiving digital training and reporting an average revenue increase of 30%. The study concludes that collaboration among government, academia, and the private sector is essential to ensure the sustainability of MSME digital transformation. Policy recommendations are also suggested to support MSMEs in adopting digital technology more effectively